The Heroic Journey of Steve Rogers in Alex Irvine’s Captain America: The First Avenger - Wardana, Saifullah Jayawisnu; Afifuddin, Muzakki (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This study is carried out with the aim of finding out how the modern heroic story that occurs in Alex Irvine's Captain America The First Avenger is still related to the theory of heroism which is based on old community stories in the form of myths, legends and folklore. This research uses Joseph Campbell's Hero's Journey theory or monomyth to analyze how the narrative in the novel follows the plot laid out in the hero's journey theory. This study takes the perspective of Steve Rogers as the main character who experienced many events according to the parts and stages mentioned in Joseph Campbell's theory. The data source in this study is Alex Irvine's literary work entitled Captain America The First Avenger, which is an adaptation of a film that was made into a novel and published in New York in 2014 by the publisher Little Brown. The data collection technique is carried out using a reading and note-taking technique that allows researchers to scan data in sources which are then classified according to what is required from the theory used. Analysis of this data shows that the narrative of the novel Captain America The First Avenger by Alex Irine follows all the stages in hero’s journey theory by Joseph Campbell.